Peace : Much More than the End of War - Cabrera Suárez, Lizandro (DIXI, 2016)
Purpose: to perform a rather crude, skeptic analysis of the future signing of the peace agreement in La Habana, Cuba with the insurgent group Fuerzas Armadas Revolucionarias de Colombia-Ejército del Pueblo (farc-ep) so that international experiences are taken into consideration. Description: this article starts with an overview of what post-conflct is through a series of questions in relation to macroeconomic problems that the State must face. Thn, international examples in which a similar experience has been lived are considered and some conditions are stablished in order not to repeat the results. It continues with the analysis of Colombian institutions engaged in war and their evolution paths are succinctly proposed. Point of view: the foregoing proves that Colombia deserves the peace awaited for so long by the entire society but with sustainable results, diffrent from those obtained in Central America. Th central thesis or point of view defended is that peace is more than a signature. It must be an integrated set of long-term actions instead of strategies structured in the heat of the moment. Conclusions: Colombia is not prepared for peace understood as social justice.
Keywords: conflct; human rights; Rule of Law; justice; post-conflct; victims